Securing aquatic food for Cambodians, now and in the future: Operational Plan 2024 - Sithirith, Mak (WorldFish, 2024)
This document charts an operational plan for what WorldFish Cambodia plans to achieve in 2024. It also highlights the key priorities, impact areas and themes the Cambodia program will target in the same year. WorldFish Cambodia works in the Mekong countries with both government and non-government entities, including the private sector. Through these collaborations, the work contributes to the sustainable development of the fisheries sector to improve livelihoods and food security. This happens through academic and action research following Cambodia’s Strategic Planning Framework for Fisheries 2015–2024 and country’s National Strategic Plan for Aquaculture Development 2016–2030 as well as WorldFish Strategies 2030.